Spain’s population census in 1860: its methodological problems. The introduction of social variables to the censuses - Vicente Gozálvez Pérez; Gabino Martín-Serrano Rodríguez (Boletín de la Asociación de Geógrafos Españoles)
The production of the first modern population censuses in Spain began with relative delay. The Spanish Statistics Commission – created in 1856 – is far from being autoindulgent when it comes to the results of its original geodemographic works. In its first two censuses (1857 and 1860), the Commission only offered the de facto population. It did not adequately define the concepts of economically active population and recognised its lack of credibility regarding the exhaustiveness of the registered population. The second part of the article studies one of the first social variables to be introduced in the census: school enrolment and literacy. In both cases, there are marked diferences in gender as a result of the discrimination against girls and women in education.